Plant science for gardeners : essentials for growing better plants - Pavlis, Robert (New Society Publishers, 2022)
"Plant Science for Gardeners is the key to growing better plants. This easy introduction to plant biology and chemistry gives you the knowledge and confidence to analyze problems, find solutions, and make better decisions in the garden to optimize plant health and productivity. Learn the science and ditch the rules!"--